Ruin probability approximations in sparre andersen models with completely monotone claims - Hansjörg Albrecher; Eleni Vatamidou (Risks, 2019)
We consider the Sparre Andersen risk process with interclaim times that belong to the class of distributions with rational Laplace transform. We construct error bounds for the ruin probability based on the Pollaczek-Khintchine formula, and develop an efficient algorithm to approximate the ruin probability for completely monotone claim size distributions. Our algorithm improves earlier results and can be tailored towards achieving a predetermined accuracy of the approximation.
Keywords: 330; completely monotone distributions; error bounds; heavy tails; hyperexponential distribution; Sparre Andersen model